(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Which are the key competencies (skills, knowledge) that a well-being manager needs to master? What existing resources can we use to avoid duplication for the purpose of designing an educational program for well-being managers? Purpose: The purpose of the research is to compare training programs for well-being managers between Slovenia and the EU and the USA. Method: A descriptive literature review is based on a conceptual structure that cross-checks educational programs, media formats, methods, approaches, and teaching and assessment strategies for well-being managers. Results: We will make a cross-section of the overview of educational programs in the EU, USA and Slovenia, to determine where the similarities between the contents of the programs and where the differences are. For each of the geographical regions (EU; USA and Slovenia) we will provide an overview of training courses and training programs. Organization: The research can have a positive impact on managers and organizations, as it revealed the content of training programs for well-being managers in order to make such training accessible to the organization. Society: Research can have a positive impact on society, as it provides an overview of educational opportunities for individuals who are interested in this field to the extent that they are also interested in a professional field. Originality: The survey provides a comprehensive overview of the training programs of well-being managers in Slovenia and the EU and the USA. Limitations/Future Research: The study was limited to articles published in Slovenia, the EU and the USA. Most access to content requires the submission of personal information.